2006
DOI: 10.1016/j.msea.2006.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of volume fraction and particle size on the microstructure and plastic deformation of Mg–Y2O3 composites

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
42
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(47 citation statements)
references
References 30 publications
5
42
0
Order By: Relevance
“…The compressive yield strength generally decreases in the materials which exhibit strong basal texture which favors the activation of twinning in the {10-12} <10-11> system [35][36][37]. However, with texture randomization, an increase in compressive yield strength was observed in Mg/Y 2 O 3 composite in the related study [38]. The current compressive yield strength improvement in AZ51 is in agreement with the reported compressive yielding variation observed in the Mg/Y 2 O 3 composite [38].…”
Section: Compressive Propertiessupporting
confidence: 83%
See 1 more Smart Citation
“…The compressive yield strength generally decreases in the materials which exhibit strong basal texture which favors the activation of twinning in the {10-12} <10-11> system [35][36][37]. However, with texture randomization, an increase in compressive yield strength was observed in Mg/Y 2 O 3 composite in the related study [38]. The current compressive yield strength improvement in AZ51 is in agreement with the reported compressive yielding variation observed in the Mg/Y 2 O 3 composite [38].…”
Section: Compressive Propertiessupporting
confidence: 83%
“…However, with texture randomization, an increase in compressive yield strength was observed in Mg/Y 2 O 3 composite in the related study [38]. The current compressive yield strength improvement in AZ51 is in agreement with the reported compressive yielding variation observed in the Mg/Y 2 O 3 composite [38]. On the other hand, a significant improvement in ultimate compressive strength was observed in AZ51/Y 2 O 3 composite when compared to the rest of the synthesized materials (see Table 3).…”
Section: Compressive Propertiesmentioning
confidence: 74%
“…Many attempts have been made to improve the mechanical properties of magnesium by developing magnesium-base metal-matrix composites, such as Y 2 O 3 /Mg, Al 2 O 3 /Mg, SiCp/Mg and Ti/Mg, during the past decades. [1][2][3][4][5] Recently, the researchers focused on the lighter reinforcements, such as graphene and carbon nanotube (CNT), to enhance the mechanical properties of Mg alloys. [6][7] Graphene, a single atomic layer of sp 2 hybridized carbon, has extraordinary electrical, thermal, and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…This texture results in an additional reinforcement effect when the stress axis is parallel to the basal plane because of the inhibition of the basal slip system (i.e. unique slip system at room temperature) [11,12]. It has been observed that the addition of ceramic particles induces a decrease of the f1 0 1 0g fibre texture and, therefore, a decrease in the yield stress and in the tension/compression asymmetry when the composite is deformed in the extrusion direction [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties at room temperature of the Mg-Y 2 O 3 composites produce by powder metallurgy has been recently studied [12]. The composite yield stress depends strongly on the intensity of the f1 0 1 0g fibre texture and decreases with the yttria volume fraction.…”
Section: Introductionmentioning
confidence: 99%